2013
DOI: 10.1080/17521882.2013.824015
|View full text |Cite
|
Sign up to set email alerts
|

Developing the leader as coach: insights, strategies and tips for embedding coaching skills in the workplace

Abstract: This article presents some practical insights, strategies and tips about how to help organisations embed leadership coaching skills in the workplace following participation by executives and managers in 'Leader as Coach' development programs. Given that organisations globally are increasingly using such programs as part of leadership development initiatives, it is important that we develop effective methodologies for teaching and embedding coaching skills in organisations. We argue that an evidence-based appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
70
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(75 citation statements)
references
References 38 publications
4
70
0
1
Order By: Relevance
“…But, for phases 1 and 2, according to the 3C model, this may not lead to success, because, inside the company, there is a lack of practice with involvement, consistency, responsibility, collaboration and positive team norms. All, too often, organizations invest time, effort and money in developing the coaching skills of their leaders and managers only to find that, despite initial high levels of enthusiasm, they fail to adopt the taught coaching skills in the workplace and end up slipping back into old command-and-control leadership behavior patterns (Grant et al, 2013). This is because ingrained behaviors are difficult to change (Prochaska, Velicier, Rossi & Goldstein, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…But, for phases 1 and 2, according to the 3C model, this may not lead to success, because, inside the company, there is a lack of practice with involvement, consistency, responsibility, collaboration and positive team norms. All, too often, organizations invest time, effort and money in developing the coaching skills of their leaders and managers only to find that, despite initial high levels of enthusiasm, they fail to adopt the taught coaching skills in the workplace and end up slipping back into old command-and-control leadership behavior patterns (Grant et al, 2013). This is because ingrained behaviors are difficult to change (Prochaska, Velicier, Rossi & Goldstein, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Grant and Hartley (2013) point out that, despite enthusiasm, money and a high level of deft skills, workplace coaching has not succeeded as much as it should because "ingrained behaviours are difficult to change" (p.102). They offer practical insights and strategies aligned with an organisation's values and goals to create a more successful implementation of leader as coach model.…”
Section: Literature In Coachingmentioning
confidence: 99%
“…A good business coach needs to be oriented to business strategy and to understand the complexities of organisations (Grant and Hartley, 2013). He or she needs to be aware of the process of reflection in the sense of bringing one's ideas to consciousness (Cain, 2009).…”
Section: Literature In Coachingmentioning
confidence: 99%
“…Senior managers (who the students were) have identified leadership styles as being one of the most important influences on organisational culture (Grant and Hartley, 2013), and students invariably integrate a study of leadership within their coaching projects. Tim's response captured the essence of the students' engagement with the story:…”
Section: Coaching Therapy Resistance and Bartlebymentioning
confidence: 99%
“…In fact, I chose Bartleby for the students to read because the story typified a range of dysfunctional personalities, the kinds a coach might encounter in the office, characters who could be role models of apathy, anger and avoidance, and therefore ideal subjects for a sustainable coaching intervention. Grant and Hartley (2013) surveyed a range of coaching skills in the workplace and found that one of the most important influences on organisational behaviour was identifying positive role models. Melville's story of a lawyer/narrator faced with a group of dysfunctional legal 13 document copiers or clerks, and in particular, his new hire Bartleby, who soon starts to say little beyond "I prefer not to" when asked to carry out any of his tasks, seemed the embodiment of a case study for coaching students.…”
Section: Coaching Therapy Resistance and Bartlebymentioning
confidence: 99%